Descendants : [an original Walt Disney Records soundtrack] [compact disc]. (Walt Disney Records, 2015)
The teenage sons and daughters of Disney's most infamous villains take the spotlight in a movie that fuses classrooms and castles to create a contemporary, music-driven story about the challenges of living up to expectations.